JEJAK PENDIDIKAN ISLAM NUSANTARA: TRANSFORMASI MASJID LANGGAR, DAN MEUNASAH DARI MASA KE MASA - Hanif Abdul Fath; Faridi Faridi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This study examines the history and dynamics of Islamic educational institutions in the Indonesian archipelago, specifically those based on mosques, langgar, and meunasah, as informal educational institutions that have served as the backbone of Islamic knowledge transmission. Employing a qualitative approach with a library research method, the study was conducted through several stages, including the identification and selection of relevant primary and secondary sources, thematic and chronological data classification, and critical-historical analysis of institutional development and transformation. The findings reveal the central role of these institutions in shaping Islamic civilization in the archipelago from the pre-colonial period to the contemporary era. Mosques functioned not only as places of ritual worship but also as centers of formal and informal education, intellectual discourse, and community empowerment. Langgar and meunasah, functioning at elementary and intermediate educational levels, played a crucial role in producing religious scholars and maintaining local Islamic identities. The transformation of these institutions has been influenced by social, political, and cultural dynamics, including colonialism, educational modernization, and the challenges of globalization. This study finds that traditional Islamic educational institutions have adopted strategic adaptations to maintain their relevance in the modern era without abandoning fundamental Islamic values. These findings provide important insights for the development of religious-based educational policies rooted in local wisdom. ABSTRAK Penelitian ini mengkaji sejarah dan dinamika lembaga pendidikan Islam Nusantara yang berbasis masjid, langgar, dan meunasah sebagai institusi pendidikan informal yang menjadi tulang punggung penyebaran ilmu pengetahuan Islam di kepulauan Indonesia. Melalui pendekatan kualitatif dengan metode kepustakaan, penelitian ini dilakukan melalui tahapan identifikasi dan seleksi sumber primer dan sekunder yang relevan, pengelompokan data secara tematik dan kronologis, serta analisis kritis-historis terhadap perkembangan dan transformasi fungsi lembaga pendidikan Islam. Penelitian ini mengungkap peran sentral ketiga lembaga tersebut dalam membentuk peradaban Islam di Nusantara dari masa pra-kolonial hingga kontemporer. Hasil penelitian menunjukkan bahwa masjid tidak hanya berfungsi sebagai tempat ibadah ritual, tetapi juga sebagai pusat pendidikan formal dan informal, diskursus intelektual, serta pemberdayaan masyarakat. Langgar dan meunasah sebagai lembaga pendidikan tingkat dasar dan menengah berperan krusial dalam mencetak kader ulama dan mempertahankan identitas keislaman lokal. Transformasi fungsi lembaga-lembaga ini dipengaruhi oleh dinamika sosial, politik, dan budaya, termasuk pengaruh kolonialisme, modernisasi pendidikan, dan tantangan globalisasi. Penelitian ini menemukan adanya adaptasi strategis lembaga-lembaga pendidikan Islam tradisional dalam menjaga relevansinya di era modern tanpa mengesampingkan nilai-nilai fundamental Islam. Temuan ini memberikan wawasan penting bagi pengembangan kebijakan pendidikan berbasis keagamaan yang berakar pada kearifan lokal.